Legal aspects of the development of the fuel and energy sector in the context of problems of energy efficiency and conservation in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
In this article, the author writes about the problem of general description to the operating normative legal acts in a sphere fuel - power complex in Republic of Kazakhstan, problems sent to the decision related to energy efficiency and energy-savings. The realization of targeted state energy conservation policy, ensure energy security of our country. The essence of this policy is to ensure a stable population and the economy with energy, more efficient use of energy resources. Energy saving today is a very topical and multifaceted problem. Since energy is one of the main sources of livelihood of our economy, needs a focused and integrated approach to solving the problem of energy conservation and energy efficiency.Key words: energy, energy efficiency, energy-savings, proceeded in energy sources, energy consumptions.